Production trend of herbicides vis-Ã -vis other pesticides in India - A, Jamaludheen; Singh, P K; Gharde, Yogita (Indian Farming, 2022)
Pesticide use in India is very low as compared to other countries. All group of pesticides and herbicides have an important role to play in Indian agriculture. Herbicides or chemical method of weed management is considered as the most effective tool to deal with the weed menace in crops. The pesticide market in India is one of the billion rupees markets of the country. Hence, understanding the production trend of various herbicides in relation to the other group of pesticides has great significance. It would help provide an overall picture of domestic production scenario of herbicides which in turn will help forecast supply-demand gap of the same.